The growth potential and bioaccumulation ability of probiotics under the exposure of different heavy metals - Abang Mohamad Moasili, Abang Mohamad Musawi; Wan Johari, Wan Lutfi; Mohd Ikhsan, Natrah Fatin; Ahmad, Siti Aqlima; Yasid, Nur Adeela; Abd. Shukor, Mohd Yunus (Universiti Putra Malaysia Press, 2019)
The presence of heavy metals in aquaculture is a major concern due to possible toxicity effects to the organisms. Bioaccumulation with bacteria is an effective and economical way to remove heavy metals from the water. The objectives of this research were to measure the growth rate of probiotics (Bacillus sp. BpChIAY [BpChIAY] and Bacillus thruingiensis, [Bt]) under different concentrations of selected heavy metals, and to determine the ability of the probiotics to bioaccumulate selected metals. Bacterial strains were grown in nutrient broth with the addition of heavy metals (Cu, Cr, Cd, Zn, Ni) at 37°C to determine the growth under exposure to heavy metals. The bioaccumulation experiment was conducted by exposing the strains' pellets to heavy metals solutions. The concentrations of heavy metals were measured using Atomic Absorption Spectroscopy (AAS). The bacterial growth percentages when grown under 2 ppm Zn, Ni and Cd for BpChIAY were 128%, 103% and 67%, and for BT, the growth rates were 97.7%, 98.8% and 36.2%, respectively. The findings showed the order of the toxicity in the order from the most toxic: Cu>Cr>Cd>Zn>Ni. Both strains were able to bioaccumulate the heavy metals, and BpChIAY was a better metal absorber than BT at the rate of 0.0539 mg/g for Zn, 0.0781 mg/g for Ni and 0.0256 mg/g for Cd.